PARTISIPASI KELOMPOK WANITA TANI (KWT) MELALUI KEGIATAN PEKARANGAN PANGAN LESTARI (P2L) DALAM UPAYA PENCEGAHAN STUNTING DI DESA ASINGI KECAMATAN TINANGGEA KABUPATEN KONAWE SELATAN - Nurjihad, Nurjihad; Alsidiq, La ode; Rosmalah, Sitti; Hartati, Hartati; Sufa, Basri (Fakultas Pertanian, Universitas Janabadra, 2024)
Stunting has become a hot issue in recent years. Stunting is a condition where a child experiences growth problems caused by a lack of nutritional intake, and it can threaten the decline in the quality of human resources in the future. The Sustainable Food Yard Program (P2L) is one of the strategic steps taken by the government to reduce the risk of stunting in Indonesia, targeting various community groups, including Women Farmers Groups. Southeast Sulawesi (Sultra) is a region at risk of experiencing stunting, with 254,546 families in Sultra being at risk. The verification and validation results of villages in 2021 in 17 districts and cities in Sultra showed that Konawe Selatan Regency had the highest number of families at risk of stunting. Out of 51,405 targeted families, 33,014 were identified as at risk of stunting (BKKBN Sultra, 2021). Asingi Village, one of the villages in the Tinanggea sub-district of Konawe Selatan Regency, Sultra Province, with an active Women Farmers Group (KWT), also plays a crucial role in implementing P2L yard activities. The focus is on improving food resilience by utilizing yard areas in this region. The level of participation of the KWT in Asingi Village is interesting to investigate. The research results indicate that the level of participation in the Women Farmers Group of Asingi Village falls into the category of moderately participative. This is observed through the participation level of the women farmers group in P2L program activities, both in participating in the implementation of activities within the group and providing input/ideas in the evaluation of P2L activities. Keywords: Stunting, Women Farmers Group, Participation, Sustainable Food Yard Program IntisariStunting menjadi isu hangat beberapa tahun ini. Stunting merupakan kondisi dimana seorang anak mengalami masalah pertumbuhan yang disebabkan oleh kekurangan asupan gizi dan bisa mengancam penurunan kualitas Sumber daya manusia dimasa yang akan dating. Program Pekarangan Pangan Lestari (P2L) merupakan salah satu langkah strategis yang diambil oleh pemerintah dalam rangka menurunkan resiko angka stunting di Indonesia diperuntukan bagi kelompok masyarakat salah satunya Kelompok Wanita Tani. Sulawesi Tenggara (Sultra) merupakan wilayah yang beresiko mengalami stunting. Sebanyak 254.546 keluarga di Sultra beresiko mengalami stunting. Hasil verifikasi dan validasi desa/kelurahan pada 2021 pada 17 kabupaten kota di Sultra menunjukan Kabupaten Konawe Selatan paling tinggi jumlah keluarga berisiko Stunting, yaitu dari 51,405 keluarga yang disasar, 33.014 keluarga diantaranya berisiko stunting (BKKBN Sultra, 2021). Desa Asingi, yang merupakan salah satu desa di kecamatan Tinanggea Kabupaten Konawe Selatan Provinsi Sultra dengan KWT yang aktif, juga memainkan peran penting dalam pelaksanaan kegiatan pekarangan P2L, yang berfokus pada peningkatan ketahanan pangan dengan memanfaatkan lahan pekarangan di wilayah ini, sejauh mana Tingkat partisipasi KWT desa Asingi Menjadi menarik untuk diteliti. Hasil penelitian ini menunjukkan bahwa tingkat partisipasi terhadap kelompok Wanita tani Desa Asingi pada kategori yang cukup Partisipatif, hal ini dilihat dari Tingkat partisipasi kelompok wanita tani dalam kegiatan program P2L yaitu Partisipasi pada Pelaksanaan kegiatan didalam kelompok dan partisipasi dalam memberi masukan ide/pendapat dalam evaluasi kegiatan P2L. Kata Kunci : Stunting, Kelompok Wanita Tani, Partisipasi, Pekarangan Pangan Lestari (P2L)